Legal Protection for Creditors Against Validity of Trade Binding Act with Loan Without Dependent Rights (Analysis of Verdict Number: 34/Pdt/2017/PT. YYK and Number : 214/Pdt.G/2014/PN.Jkt Sel) - Nina Trisnowati (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2020)
Credit, which was previously considered taboo, is now a necessity in society. Everyone is looking for convenience for credit without knowing the risks and impacts that will occur in the future. The most important element of credit (debt) is the trust of the creditor towards the borrower as the debtor. Sale and Purchase Agreement (hereinafter referred to as PJB) is an agreement between a seller to sell his property to a buyer made with a notarial deed. Cases that occurred in Yogyakarta High Court Decision Number 34 / Pdt /2017/PT.YYK and District Court Decision Number 214 / Pdt, G / 2014 / PN. Jkt.Sel is a case of debt receivable with collateral for a certificate of land rights and the parties poured their agreement into the Sale and Purchase Binding Act (PPJB) and the Selling Power of Attorney, considering that after the two decisions, there was an outstanding debt problem, while the debtor was still have not been able to repay their debts to creditors, with guarantees of certificates of land rights without mortgage. The purpose of this study was to analyze the judges' consideration of the decision Number 34 / Pdt /2017/PT.YYK with Decision Number 214 / Pdt.G / 2014 / PN. Jkt Cell regarding sale and purchase agreement. analyze the legal protection for creditors against the validity of the deed of sale and purchase agreement with a loan without mortgage. analyze repayment by defaulting debtors relating to debts and loans without mortgages. The method used in this study is a normative juridical method, analyzed Normatively Qualitatively, The results of the study show that in Decision Number 34 / Pdt /2017/PT.YYK which states are null and void and do not have the power to bind an authentic deed regarding the